The effect of subcutaneous and sublingual birch pollen immunotherapy on birch pollen–related food allergy: a systematic review - Kallen, E. J. J.; Welsing, P. M. J.; Löwik, J. M.; Van Ree, R.; Knulst, A. C.; Le, T. M. (Frontiers in Allergy, 2024)
Birch pollen-related food allergy (BPFA) is the most common food allergy in birch endemic areas such as Western and Central Europe. Currently, there is no treatment available for BPFA. Due to the crossreactivity between birch pollen and a range of implicated plant foods, birch pollen allergen immunotherapy (AIT) might be effective in the treatment of BPFA. We systematically evaluated the effectiveness of birch pollen-specific subcutaneous or sublingual immunotherapy on BPFA.A search was performed in PubMed, Embase and Cochrane library. Studies were independently screened by two reviewers against pre-defined eligibility criteria. The outcomes of interest were change in 1) severity of symptoms during food challenge, 2) eliciting dose (ED) and 3) food allergy related quality of life (FA-QoL). The validity of the selected articles was assessed using the Revised Cochrane risk of bias tool. We focused on studies with the lowest risk of bias and considered studies with a high risk of bias as supportive. Data were descriptively summarized.Ten studies were selected including 475 patients in total. Seven studies were categorized into high risk of bias and three into moderate risk of bias. The three moderate risk of bias studies with a total of 98 patients, reported on severity of symptoms during challenge and including the ED. Compared to the control group, improvement in severity of symptoms was observed during challenge in 2/3 studies and on eliciting dose in 1/3 studies. Only one study investigated the effect of birch pollen AIT on FA-QoL and showed that there was no significant difference between patients receiving SCIT or placebo. Of the seven supportive studies four had an control group and of those, three showed improvement on both severity of symptoms and ED. None of the supportive studies investigated the effect on FA-QoL.This systematic review shows that there is not enough evidence to draw firm conclusions about the effect of AIT on BPFA Future research is warranted using robust clinical studies including long-term effects, QoL and multiple BPFA relates foods.